Entrepreneurial Acumen and Financial Literary of Self-employed Rural Mothers - Pabelona, Rechie B. (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study was to evaluate the financial literacy and entrepreneurial prowess of rural mothers who work for themselves. One hundred fifty eight (158) self-employed rural mothers made up the study's sample. Self-employed rural mothers were found to have low interpersonal skills and low levels of critical and practical thinking skills, with mean scores of 2.37 and 2.61, respectively, and moderate levels of entrepreneurial skills in terms of personal characteristics and practical skills, with mean scores of 2.89 and 3.41 and 3.41 and 2.89 respectively. In terms of actual financial knowledge and self-perceived financial knowledge, the respondents' levels of financial literacy are both ambiguous, with means of 3.2036 and 3.5048, respectively. It is highly advisable to take short-term courses like the training that DTE provides to all SMEs regarding managing a business. Financial literacy and entrepreneurial skill have a strong association. It shows that there is a strong correlation (r =.251*) between self-perceived financial knowledge and actual financial knowledge. The level of association between self-perceived financial knowledge and business acumen was then quite strong (r =.554**).  Finally, there is a strong correlation (r =.539**) between actual financial knowledge and entrepreneurial skill. This result demonstrates that there is a great need to raise the financial literacy of rural mothers who work for themselves. Governments, academia, and those in the financial industry should collaborate to create a better financial future for rural women who work for themselves as well as for the nation as a whole. The link discovered should be further supported by future study.